Feeding on toxic prey. The praying mantis (Mantodea) as predator of poisonous butterfly and moth (Lepidoptera) caterpillars. (1st June 2017) - Mebs, Dietrich; Wunder, Cora; Pogoda, Werner; Toennes, Stefan W.
Abstract: Caterpillars of the monarch butterfly, Danaus plexippus, feed on milkweed plants, Asclepias spp. (Apocynaceae), and sequester their toxic cardenolides aimed at deterring predators. Nevertheless, Chinese praying mantids, Tenodera sinensis, consume these caterpillars after removing the midgut ("gutting") including its plant content. In the present study, monarch caterpillars raised on A. curassavica, and those of the death's-head hawkmoth, Acherontia atropos, raised on Atropa belladonna containing atropine, were fed to mantids, Hierodula membranacea, which removed the gut of both species discarding about 59% of cardenolides and more than 90% of atropine, respectively. The ingestion of these compounds produced no apparent ill effects in the mantids and both were excreted with faeces. On the other hand, when mantids were fed with larvae of two moth species, Amata mogadorensis and Brahmaea certia, raised on non-poisonous host plants, the mantids showed the same gutting behaviour, thereby discarding indigestible plant material. As polar compounds, e.g. cardenolides and atropine, are not absorbed from the mantids midgut and do not pass the gut membrane, this enables the mantids to feed on toxic prey. Highlights: The praying mantis feeds on toxic caterpillars and discards the intestines. However, the mantis still ingests toxins, which are secreted later with faeces. But the mantis shows the same behaviour when feeding on non-toxic caterpillars. To get rid of plant material in the intestines seems to be the main reason.